Analysis of Gender Based Variations in Leadership Styles and its Efficacy - Khattak, Khalid Usman Khan; Khattak, Khanzadi Fatima; Khattak, Mamoon Khan (Annals of Human and Social Sciences, 2023)
The central objective of this study has been to explore the gender based variances in decision making patterns and its effectiveness. Allah Almighty has created human being with variant potentials and capabilities. Men and women do have a gender based varying status and role to perform in a society according to its expectations. A number of 60 respondents were face-to-face interviewed consisting of 30 male managers and 30 female managers working in different organizations having at least one-year managerial experience. The sampling area has been the district Kohat of Khyber Pakhtunkhwa and Islamabad, the Federal Capital of the Islamic Republic of Pakistan. The findings of study have shown that there were variations in decision making, involvement of employees in the organizational processes, consultation-status of employees in decision making, leadership choices and pace of decision making etc. with respect to differences of males and females. Female leaders were at advantage in making consultation-based decisions, while male leaders were at advantage of implementing decisions gradually. It is recommended that the leaders should adopt democratic leadership style for effectiveness by involving their employees in decision making processes.